Structure and stability of synthetic surfactant aggregates: Ion association selectivity to interfaces and vesicle formation - Mortara, Laura (2023)
Specific ion effect defines a variety of phenomena in physical chemistry and biology, from the stability of colloidal suspensions to enzymatic activity and ligand-receptor binding. Establishing a rigorous scientific interpretation of these effects has kept scientists busy for over a century. Nevertheless, a complete description of the specificities of ion interactions with the solute surface still needs to be completed. In the spontaneous aggregation of amphiphiles, the hydrophobic effect depends, almost exclusively, on the difference of free energy between the exposed areas of the hydrocarbon chains of the natural lipid or synthetic surfactant in solution or in the aggregate. The detailed structure of the aggregate, the chain order, and the viscosity depend critically on the surfactant\'s molecular structure and the medium composition. We showed that, for zwitterionic micelles, there is no specific anion effect on the overall micelle hydration, but there is a specific anion effect on the thermodynamics of micelle formation. We also showed that the degree of counterion partitioning in these zwitterionic micelles could be directly correlated to the dehydration of apolar moieties of hydrotropic anions upon interface interaction. Still, on ion effects, the competition between chloride and bromide interaction in cationic surfactant monolayers was directly quantified and modeled. Lastly, we showed the formation of vesicular aggregates by a novel imidazolium-based surfactant. Thermal phase behavior of this surfactant was characterized and the phase transition temperature significantly differed from a similar commercially available surfactant with the same alkyl tail length. The work developed in this thesis, using two different systems, i.e., zwitterionic and cationic surfactants, has clarified aspects related to specific ion effects and the formation of micellar and vesicular aggregates.